Research in progress: put the orphanage out of business. Issue 10 (21st February 2013) - Bush, Andrew; Anthony, Gisela; Barbato, Angelo; Cunningham, Steve; Clement, Annick; Epaud, R; Gilbert, Carlee; Goldbeck, Lutz; Kronfeld, Kai; Nicholson, Andrew G; Schwerk, Nicolaus; Griese, Matthias; et al.
Abstract : Paediatric interstitial lung disease (ILD) is rare and diverse, meaning no single centre will see sufficient children to perform the studies needed to make progress. This EU FP-7 grant will standardise the evaluation of these rare conditions by establishing pan-European multidisciplinary expert panels and establish consensus on treatment protocols and standard operating procedures across Europe. We will work with patient groups to determine optimal treatment end-points and biomarkers. A biobank will be established as a Europe-wide resource for mechanistic studies. Ultimately we aim to do the first randomised controlled trial of a pharmacological treatment in paediatric ILD.